The Impact of Landfill Operations on Borehole Water Quality - Lyndon N. A. Sackey; Rita Kwablah; Lawrencia S. Y. Agyemang (The Scientific World Journal)
Water is crucial for life, and although groundwater is considered safe, it can degrade due to inadequate source protection and inefficient resource management. The aim of the study was to assess the impact of landfill operations on water quality from selected landfill sites. Spectrometry analytical techniques were used to assess the physicochemical parameters of the samples. The study found that while Salmonella was absent in most samples, E. coli and total coliforms were present, making the water unsafe for domestic use. Although turbidity, pH, temperature and other parameters were within acceptable GSA/WHO levels, total coliform and E. coli raise concerns about faecal contamination and potential health risks. Cadmium was absent in all samples, but chromium, lead, arsenic and mercury were detected. These heavy metals could pose health hazards to consumers. The samples showed no risk of noncarcinogenic and carcinogenic risk to consumers, but then there is a potential health risk to consumers over time due to bioaccumulation. Regular monitoring and periodic assessments are recommended to ensure water safety. Proper waste management practices in landfill areas can minimize potential impacts on water quality, highlighting the need for continuous monitoring and assessment. The municipal authorities can inform residents of the situation and put in policies to protect human health. The results could help residents know the level of contamination of water from their boreholes and the necessary precautions to take to reduce their health impact. A treatment system can be developed in detail to their peculiar need.